Pengaruh Pengetahuan Kewirausahaan dan Kepribadian Wirausaha Terhadap Keberhasilan Usaha Gula Aren di Desa Luyo - Solihin, Andi; Asrandi, Asrandi; Alwi, Muhammad (Institut Agama Islam Negeri Parepare, 2025)
This study aims to analyze the influence of entrepreneurial knowledge and entrepreneurial personality on the business success of palm sugar enterprises in Luyo Village, Polewali Mandar Regency. The research employed a quantitative method with a survey approach. A total of 30 palm sugar entrepreneurs were selected as respondents using a simple random sampling technique. Research instruments were tested for validity and reliability, showing that all items were valid and reliable. Data analysis was conducted using multiple linear regression. The results reveal that entrepreneurial knowledge does not have a significant effect on the business success of palm sugar enterprises, as indicated by a significance value of 0.414 and a t-value of 0.830, which is lower than the critical t-table value of 2.051. Conversely, entrepreneurial personality has a significant and positive influence on business success, with a significance value of 0.014 and a t-value of 2.618, exceeding the t-table threshold. These findings suggest that formal entrepreneurial knowledge may not play a major role in determining the success of traditional businesses such as palm sugar production. Instead, personal traits like persistence, risk-taking, and creativity are more influential in driving entrepreneurial success. The study contributes to a contextual understanding of how internal characteristics affect small business outcomes in traditional, resource-based settings.